The secret poisoner: a century of murder - Stratmann, Linda (Yale University Press, 2016)
"Murder by poison alarmed, enthralled, and in many ways encapsulated the Victorian age. Linda Stratmann's dark and splendid social history reveals the nineteenth century as a gruesome battleground where poisoners went head-to-head with authorities who strove to detect poisons, control their availability, and bring the guilty to justice. She corrects many misconceptions about particular poisons and documents how the evolution of issues such as marital rights and the legal protection of children impacted poisonings. Combining archival research with a novelist's eye, Stratmann charts the era's inexorable rise of poison cases both shocking and sad"--